2022
DOI: 10.5603/imh.2022.0025
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries, oral hygiene status and treatment needs of fishermen and non-fishermen population in South Goa, India

Abstract: Background: Occupation plays a major role in the well-being of an individual and has an influence on oral health. Fishing is one such occupation that entails a lot of physical labour and encourages habits that lead to poor oral health. Therefore, it is critical to shed light on the oral health of this isolated population to improve their quality of life by various means. The aim of the study was to assess and compare the prevalence of dental caries, oral hygiene status and treatment needs of fisherman and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In general, out of 22 included observational studies, 16 studies were rated as high quality [ 12 , 20 , 36 , 38 , 59 , 61 68 , 70 72 ], 5 studies had moderate quality [ 11 , 35 , 37 , 60 , 69 ] and only one study was rated as low quality due to not presenting data and weak methodological design [ 39 ] ( S2 Appendix ). When assessing the quality of RCT by the revised Cochrane risk-of-bias tool, the overall risk-of-bias judgement of both studies were to have some concern on risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, out of 22 included observational studies, 16 studies were rated as high quality [ 12 , 20 , 36 , 38 , 59 , 61 68 , 70 72 ], 5 studies had moderate quality [ 11 , 35 , 37 , 60 , 69 ] and only one study was rated as low quality due to not presenting data and weak methodological design [ 39 ] ( S2 Appendix ). When assessing the quality of RCT by the revised Cochrane risk-of-bias tool, the overall risk-of-bias judgement of both studies were to have some concern on risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…One study investigated the prevalence of dental caries among smoker and non-smoker fishermen with caries prevalence of 46.5% and 65.8%, respectively [ 63 ]. Five studies demonstrated high prevalence of dental caries with 82% [ 59 ], 82.6% [ 65 ], 90.9% [ 60 ], 55% [ 67 ] and periodontal diseases (99% [ 67 ]; 97.2% [ 60 ]; 85.4% [ 65 ], 100% [ 68 ] among fishermen. The prevalence of dental caries and periodontal diseases among seafarers were 88% and 75.1%, respectively [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations